[1907 Basketball Teams] - Frank Aston::::::photographer::: (1907)
1907 basketball teams; women's team seated front; men's team standing behind; basketball painted 'CPS '07.' 1 addressed to 'Miss Mae Brew'; image published in Polytechnic Journal (v.3, no. 5, Feb. 1908)